Mechanical Properties of the Every Second Matters for Mothers-Uterine Balloon Tamponade (ESM-UBT) Device: In Vitro Tests - Mollazadeh-Moghaddam, Kamyar; Dundek, Michelle; Bellare, Anuj; Borovac-Pinheiro, Anderson; Won, Alice; Burke, Thomas F. (American Journal of Perinatology Reports, 2019)
Objective Postpartum hemorrhage (PPH) is the most common cause of maternal mortality and morbidity worldwide, most of which occurs in resource-poor settings. Placement of a uterine balloon may be life-saving in uncontrolled PPH. The Every Second Matters for Mothers-Uterine Balloon Tamponade (ESM-UBT) device is an ultra-low-cost uterine balloon designed for global access. The purpose of this study was to evaluate the mechanical properties of the ESM-UBT device.Study design Intraluminal pressures, diameters, and burst volumes of condom uterine balloons and Foley catheter balloons of ESM-UBT devices were measured in open air and inside uterus models. Condom uterine balloons were tested with uterus model sizes of 100, 250, and 500mL. The condom-catheter O-ring attachment tensile strength was also evaluated.Results All 28 samples of ESM-UBT condom uterine balloons maintained their integrity for at least 3 hours when subjected to pressures of 200 mm Hg or greater across each of the tested uterine volumes. No Foley catheter balloons burst after instillation of 30mL, O-rings withstood forces of 15.4 ± 2.1 N, and condom uterine balloons stretched to 35.8 ± 2.1 cm without loss of integrity.Conclusion The mechanical properties of the ESM-UBT device make it attractive for scale across resource-poor settings.
Keywords: uncontrolled postpartum hemorrhage; uterine balloon tamponade; mechanical properties; medical device